Healthy dietary patterns, biological aging, and kidney stones: evidence from NHANES 2007–2018 - Wei, Chengcheng; Yang, Qian; He, Jingke; Luo, Yu; Han, Kun; Li, Junkun; Su, Shuai; Zhang, Jindong; Wang, Hongxing; Wang, Delin (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the comprehensive association between healthy dietary patterns, biological aging, and kidney stones in a large population-based cohort.MethodsWe analyzed data from 6 cycles of NHANES surveys from 2007 to 2018 and included a total of 26,755 participants. The association was examined using logistic regression, restricted cubic splines, and a mediation model. Machine learning with Shapley Additive Explanations (SHAP) was used to determine the relative importance of dietary factors. Sensitivity analysis was conducted to validate the stability of the results.ResultsA higher healthy dietary score was significantly associated with a reduced risk of kidney stone prevalence, as indicated by the Alternative Healthy Eating Index (AHEI) (OR = 0.76, 95% CI 0.69–0.84), the Dietary Approaches to Stop Hypertension Index (DASHI) (OR = 0.67, 95% CI 0.58–0.77), the Healthy Eating Index 2020 (HEI-2020) (OR = 0.80, 95% CI 0.72–0.89), and the Mediterranean Diet Index (MEDI) (OR = 0.81, 95% CI 0.73–0.89). Conversely, higher aging indicators were associated with an increased risk of kidney stones, including the following: Klemera-Doubal Method Age (KDMAge) (OR = 2.40, 95% CI 1.70–3.37) and Phenotypic Age (PhenoAge) (OR = 2.36, 95% CI 1.75–3.19). Mediation analyses suggested that aging indicators significantly mediated the relationship between healthy dietary patterns and kidney stones. Machine learning with SHAP revealed the relative importance of dietary patterns and specific dietary components in this association. The sensitivity analysis was largely consistent with the primary analyses.ConclusionThese findings provide valuable insights into the complex interplay between dietary patterns, biological aging, and the risk of kidney stone. Promoting healthy dietary patterns may be an effective strategy for kidney stone prevention, potentially through the modulation of biological aging processes.